Controlling exciton transport in monolayer MoSe2 by dielectric screening. Issue 1 (3rd September 2019) - Hao, Shengcai; Bellus, Matthew Z.; He, Dawei; Wang, Yongsheng; Zhao, Hui
Abstract : Exciton transport in a two-dimensional semiconductor is controlled by placing a top dielectric layer. Abstract : Due to their atomic thinness with reduced dielectric screening, two-dimensional materials can possess a stable excitonic population at room temperature. This is attractive for future excitonic devices, where excitons are used to carry energy or information. In excitonic devices, controlling transport of the charge-neutral excitons is a key element. Here we show that exciton transport in a MoSe2 monolayer semiconductor can be effectively controlled by dielectric screening. A MoSe2 monolayer was partially covered with a hexagonal boron nitride flake. Photoluminescence measurements showed that the exciton energy in the covered region is about 12 meV higher than that in the uncovered region. Spatiotemporally resolved differential reflection measurements performed at the junction between the two regions revealed that this energy offset is sufficient to drive excitons across the junction for about 50 ps over a distance of about 200 nm. These results illustrate the feasibility of using van der Waals dielectric engineering to control exciton transport and contribute to understanding the effects of the dielectric environment on the electronic and optical properties of two-dimensional semiconductors.